The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12909-018-1258-3
|View full text |Cite
|
Sign up to set email alerts
|

Internal diseases encountered by dental students while treating dental patients during undergraduate training

Abstract: BackgroundThe number of internal diseases, disorders and syndromes (IMDDSs) encountered in dental practice is increasing. Dentists report to feel ill prepared by their undergraduate dental training for the management of IMDDSs. To increase the effectiveness of internal medicine training at dental school it might be necessary to focus on IMDDs encountered by dental students. The aim of our study was to identify IMDDSs dental students come across while treating dental patients during the clinical years of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Cardiovascular disease (37.9%), allergy (32.3%), mental health disorders (29.4%) musculoskeletal (23.0%) endocrine (22.4%) and respiratory disease (17.8%) constituted the most common conditions reported with the pattern of medication usage paralleling the diseases reported. This is in keeping with other studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and also re ects the most common chronic diseases in Australia [27]. Each of those conditions and associated medication use can not only contribute to the presentation of numerous intraoral pathosis but also affect the safe delivery of dental treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Cardiovascular disease (37.9%), allergy (32.3%), mental health disorders (29.4%) musculoskeletal (23.0%) endocrine (22.4%) and respiratory disease (17.8%) constituted the most common conditions reported with the pattern of medication usage paralleling the diseases reported. This is in keeping with other studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and also re ects the most common chronic diseases in Australia [27]. Each of those conditions and associated medication use can not only contribute to the presentation of numerous intraoral pathosis but also affect the safe delivery of dental treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Cardiovascular disease (37.9%), allergy (32.3%), mental health disorders (29.4%) musculoskeletal (23.0%) endocrine (22.4%) and respiratory disease (17.8%) constituted the most common conditions reported with the pattern of medication usage paralleling the diseases reported. This is in keeping with other studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and also re ects the most common chronic diseases in Australia [25]. Each of those conditions and associated medication use can not only contribute to the presentation of numerous intraoral pathosis but also affect the safe delivery of dental treatment.…”
Section: Discussionsupporting
confidence: 88%
“…A previous German study found that undergraduate dental students treat a high number of patients with systemic internal diseases during their clinical semesters [15]. Thereby, it was also concluded that more studies focusing on medical topics in dental education would be necessary [15].…”
Section: Comparison With Available Literaturementioning
confidence: 99%
“…Against this background, it is of increasing relevance for undergraduate dental students to be prepared for future challenges in the dental care of patients with general diseases, conditions and/or medications [15]. Thereby, awareness and knowledge of antimicrobial prophylaxis need to be strongly emphasized [16].…”
Section: Introductionmentioning
confidence: 99%